Psychobiotic effects of probiotics and prebiotics - V. T. Ivashkin; K. V. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2018)
Aim of review. The review is devoted to the effects of probiotics and prebiotics on emotional, cognitive, systemic and central spheres of psychophysiological activity in animals and humans. Microbiome is a basis of the gut-brain axis. The bacterial colonization of the gut is initiated at the moment of delivery and represents incomplete copy of maternal microbiota. Intestinal microbiome is a factor of hypothalamic-pituitary-adrenal axis formation that is involved in regulation of immunomodulation, lipid metabolism, energy balance and electrophysiologic activity of enteric nervous system. Summary. Comparison of probiotic affects in animal and human experimental studies demonstrates their equivalence. Many experimental data indicative of relation of probiotic intake and patients’ mood are accumulated. The effect of probiotics on cortisol level was demonstrated. The proof of possible immunologic effects of probiotics at irritable bowel syndrome that is associated with gut-brain signal axis disorders and microbiome changes was received. Attempts to reveal intrinsic mechanisms of positive emotional shifts in humans are of a great interest. Ability of psychobiotics to influence the depth of emotions is confirmed. Conclusion. Psychobiotics are capable to provide positive impact on patients’ mood. Addition of behavioral criteria of concern, cognitive control and suppressed mood to the studies will broaden spectrum and palette of a self-assessment of study participants. At a systemic level suppression of cortisol and proinflammatory cytokines production by psychobiotics maintain the positive effect on the mood due to reduction of systemic inflammation severity.